Pushing Boundaries with Deep Generative Models: Innovations and Applications of VAEs and GANs (Advances in Deep Learning Techniques, 2022)
This paper delves into the cutting-edge realm of deep generative models, specifically focusing on variational autoencoders (VAEs) and generative adversarial networks (GANs). We explore the innovations and applications that have pushed the boundaries of these models, enabling them to generate realistic data across various domains. Beginning with an overview of VAEs and GANs, we delve into recent advancements such as conditional generation, style transfer, and multimodal synthesis. We discuss how these models have been utilized in diverse fields including image generation, text-to-image synthesis, and drug discovery. Furthermore, we examine challenges and future directions in the field, emphasizing the importance of ethical considerations and interpretability. Through this comprehensive analysis, we illustrate the immense potential of VAEs and GANs in driving innovation and fostering novel applications across disciplines.
Keywords: deep generative models; variational autoencoders; VAEs; generative adversarial networks; GANs; conditional generation; style transfer; multimodal synthesis; applications; innovations